Understanding Love in Filipino Culture: An Examination of Indigenous Perspectives and Cultural Reflections - Ramos, Christine Carmela (Conatus - Journal of Philosophy, 2025)
This study explores Filipino cultural and political contexts through the lens of Filipino Indigenous thought, focusing on the philosophical underpinnings of the concept of "loob" and its influence on the understanding of love (pag-ibig). "Loob" is examined as a route to achieving harmony with others and nature, aiming for unity with the divine. The research distinguishes between two key dimensions: the analytic (interior) and the synthetic (holistic). The analytic dimension emphasizes the inherent goodness within individuals. In contrast, the synthetic dimension offers a holistic perspective, crucial for addressing Filipinos’ multifaceted challenges in a diverse and pluralistic society. The paper highlights the importance of incorporating nonviolence into literature, the arts, and education, arguing that this integration fosters mature humanity within a rapidly evolving global consciousness. The articulation of nonviolence in these domains is presented as a crucial step toward achieving a more just and harmonious society. Furthermore, the study draws a philosophical comparison between the nonviolent efforts of Corazon Aquino and Mahatma Gandhi, examining their roles in pursuing freedom through nonviolence. Gandhi’s application of ahimsa (doing no harm) as a tool for civil protest is analyzed in the context of the dynamic processes of societal control and justice he confronted. His leadership in resisting colonial rule, leading the Indian rebellion, and challenging discriminatory policies is contrasted with Aquino’s efforts toward political and social change. The paper argues that Gandhi’s philosophical approach aligns closely with Aquino’s strategies for emancipatory political achievement and justice through nonviolence, underscoring their shared commitment to these enduring ideals.